Linear array beampattern gain optimization techniques - Nagi F. (IEEE Computer Society, 2023)
The work describes here uses optimization techniques to increase the gain of a uniform linear array's beampattern when some of its elements fails. The optimization criteria evaluates the weights of the remaining elements so as to restore the gain as closely as possible to the reference beampattern. LMS and goal programming methods are used to evaluate the weights of the remaining array elements. In the LMS algorithm the error between the reference and the iterated beampattern is reduced. In the goal attaining algorithm the goal of optimization is set to the reference pattern. The comparison between the two techniques reveals that in general the goal programming algorithm perform better in terms of the SNR of the beampattern beamwidths. 2001 IEEE.